Short-term effects of winter warming and acidification on phytoplankton growth and mortality: more losers than winners in a temperate coastal lagoon - Domingues, Rita B. (2022)
Changes in temperature and CO2 are typically associated with climate change, but they also act on shorter time scales, leading to alterations in phytoplankton physiology and community structure. Interactions among stressors may cause synergistic or antagonistic effects on phytoplankton dynamics. Therefore, the main goal of this work is to understand the short-term isolated and interactive effects of warming and high CO2 on phytoplankton nutrient consumption, growth, production, and community structure in the Ria Formosa coastal lagoon (southern Portugal). We performed microcosm experiments with temperature and CO2 manipulation, and dilution experiments under temperature increase, using winter phytoplankton assemblages. Phytoplankton responses were evaluated using inverted and epifluorescence microscopy. Overall, phytoplankton growth and microzooplankton grazing on phytoplankton decreased with warming. Negative antagonist interactions with CO2 alleviated the negative effect of temperature on phytoplankton and cryptophytes. In contrast, higher temperature benefited smaller-sized phytoplankton, namely cyanobacteria and eukaryotic picophytoplankton. Diatom growth was not affected by temperature, probably due to nutrient limitation, but high CO2 had a positive effect on diatoms, alleviating the effect of nutrient limitation. Results suggest that this winter phytoplankton assemblage is well acclimated to ambient conditions, and short-term increases in temperature are detrimental, but can be alleviated by high CO2.